1987
DOI: 10.1002/1097-0142(19870815)60:4<741::aid-cncr2820600406>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cystic hygroma and lymphangioma with the use of bleomycin fat emulsion

Abstract: Of the several types of treatment for cystic hygromas and lymphangiomas, surgical excision has been the preferred treatment. However, there is a high recurrence rate because lymphangiomas tend to infiltrate the surrounding tissues. Bleomycin in a microsphere-in-oil (S/O) emulsion was used in this study as a sclerosing agent for lymphangiomas. Experimental studies using domestic rabbits showed that the bleomycin emulsion caused more marked fibrotic changes at the injection site than other formulations, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 6 publications
2
52
1
2
Order By: Relevance
“…55 Because of concerns regarding associated complications of pulmonary fibrosis its use was limited. There is now increasing evidence that reduced dosing separated by 2 weeks between sessions, with no more than 5 mg kg 21 lifetime dose, can limit this complication.…”
Section: 54mentioning
confidence: 99%
“…55 Because of concerns regarding associated complications of pulmonary fibrosis its use was limited. There is now increasing evidence that reduced dosing separated by 2 weeks between sessions, with no more than 5 mg kg 21 lifetime dose, can limit this complication.…”
Section: 54mentioning
confidence: 99%
“…Comparative studies of treatments between the bleomycin S/O emulsion and surgery indicated that injection therapy of the bleomycin S/O emulsion would be more beneficial than surgical excision. 13) As for the O/W emulsion, large logPCoct values or a high lipophilicity are required for drugs in order to keep them in the O/W emulsion. One of the most interesting potential approaches to prolong the retention time in emulsions after local injection is to increase the lipophilicity of the drug by chemical modification, leading to a prodrug.…”
Section: Distribution Characteristics Of Lipid Emulsions or Liposomesmentioning
confidence: 99%
“…12 Recurrence of symptoms with incomplete excision is possible. 16 Injection of sclerotic agents such as alcohol and bleomycin into lymphangiomas has also been described as the non-surgical treatment. However, induration of the cyst and infection often complicate this procedures.…”
Section: Discussionmentioning
confidence: 99%